An investigation of DEET-insensitivity in Aedes aegypti - Stanczyk, Nina M. (2011)
N,N-Diethyl-m-toluamide (DEET) is one of the most effective and commonly used mosquito repellents. However, during laboratory trials a small proportion of mosquitoes are still attracted by human odours despite the presence of DEET. In this study behavioural assays identified Aedes aegypti females that were insensitive to DEET. The selection of either sensitive or insensitive groups of females with males of unknown sensitivity over several generations resulted in two populations with different proportions of insensitive females. Crossing experiments showed the ‘DEET-insensitivity’ trait to be dominant. In addition to the finding of heritable DEET-insensitivity, unselected culture mosquitoes were shown to change their sensitivity to DEET after brief pre-exposure to the repellent. Female mosquitoes that were sensitive to DEET when first tested became insensitive when retested. Electroantennography showed that mosquitoes that were insensitive to DEET had a reduced response to DEET compared with mosquitoes that were sensitive to it. This was the case both for culture mosquitoes displaying insensitivity to DEET after brief pre-exposure to it, and for the sensitive and insensitive lines selected for several generations. Single sensillum recordings of the selected lines identified DEET-sensitive sensilla in the sensitive line that did not respond to DEET in the insensitive line. This study suggests that behavioural insensitivity to DEET in Ae. aegypti is a genetically determined dominant trait, which can also be temporarily induced by pre-exposure, and resides in changes in sensillum function. These results highlight the necessity for careful monitoring of DEET-insensitivity in the field, and caution when designing laboratory methods for repellency assays.